A locus for primary ciliary dyskinesia maps to chromosome 19q. Issue 4 (1st April 2000) - Meeks, M; Walne, A; Spiden, S; Simpson, H; Mussaffi-Georgy, H; Hamam, H D; Fehaid, E L; Cheehab, M; Al-Dabbagh, M; Polak-Charcon, S; Blau, H; O'Rawe, A; et al.
Abstract : Primary ciliary dyskinesia is an autosomal recessive condition characterised by chronic sinusitis, bronchiectasis, and subfertility. Situs inversus occurs in 50% of cases (Kartagener syndrome). It has an estimated incidence of 1 in 20 000 live births. The clinical phenotype is caused by defective ciliary function associated with a range of ultrastructural abnormalities including absent dynein arms, absent radial spokes, and disturbed ciliary orientation. The molecular genetic basis is unknown. A genome scan was performed in five Arabic families. Using GENEHUNTER, a maximal multipoint lod score (HLOD) of 4.4 was obtained on chromosome 19q13.3-qter at α (proportion of linked families) = 0.7. A 15 cM critical region is defined by recombinations at D19S572 and D19S218. These data provide significant evidence for a PCD locus on chromosome 19q and confirm locus heterogeneity.